Yield Response to Nitrogen Management in a Corn-Soybean Sequence in North Central Kansas – 2021 Season - A. A. Correndo; O. Lanza Lopez; L. F. A. Almeida; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2022)
The aim of this study was to evaluate the response of corn (Zea maysL.) grain yield to nitrogen (N) fertilizer application and its residual effect on soybean [Glycine max(L.) Merr.] seed yield. During the 2021 growing season, a corn-soybean rotation study was continued at Scandia, KS (USA), evaluating the effect of five N fertilizer rates (0, 53, 107, 161, and 214 lb N/a) applied in corn under both dryland and irrigated conditions. Average corn grain yields ranged from 124 to 147 bu/a for dryland, and from 159 to 203 bu/a for irrigated conditions. However, no significant grain yield response to fertilizer N rate was observed in either dryland or irrigated plots. Average soybean seed yields varied from 46 to 59 bu/a for dryland and from 76 to 86 bu/a for irrigated conditions. A significant effect of previous corn fertilizer N rate was observed under dryland conditions. Also, a significant positive soybean seed yield effect with corn maximum N rate (214 lb N/a) with respect to rates of 53 and 107 lb N/a. No residual effects of previous corn N rate were observed on soybean yields under irrigation.
Keywords: yield response; maize; soybean; productivity; dryland; irrigation; corn